A preliminary study of the effects of mindfulness‐based cognitive therapy on structural brain networks in mood‐dysregulated youth with a familial risk for bipolar disorder. Issue 9 (22nd November 2021) - Yang, Jing; Lei, Du; Suo, Xueling; Tallman, Maxwell J.; Qin, Kun; Li, Wenbin; Bruns, Kaitlyn M.; Blom, Thomas J.; Duran, Luis Rodrigo Patino; Cotton, Sian; Sweeney, John A.; Gong, Qiyong; et al.
Abstract: Background: Mindfulness‐based cognitive therapy for children (MBCT‐C), as a psychotherapeutic intervention, has been shown to be effective for treating mood dysregulation (MD). While previous neuroimaging studies of MD have reported both pre‐treatment structural and functional alterations, the effects of MBCT‐C on brain morphological network organisation has not been investigated. Methods: We investigated brain morphological network organisation in 10 mood‐dysregulated youth with familial risk for bipolar disorder and 15 matched healthy comparison youth (HC). Effects of 12 weeks of MBCT‐C were examined in the mood‐dysregulated youth. Topological properties of brain networks used for analyses were constructed based on morphological similarities in regional grey matter using a graph‐theory approach using MRI data. Results: At baseline, compared with the HC group, the mood‐dysregulated group exhibited increased global efficiency ( E glob ), decreased path length ( L p ), and abnormal nodal properties, mainly in the limbic system. Right temporal pole alterations at baseline predicted change in Child and Adolescent Mindfulness Measure scores after treatment. The mood‐dysregulated group showed significant decreases in both the E glob and L p metrics after MBCT‐C, suggesting an improved capacity for optimal information processing. Changes in L p were correlated with changes in Emotion Regulation Checklist scores. Our results show significant topological alterations in the mood‐dysregulated group as compared to controls at baseline. After MBCT‐C, disrupted topological properties in the mood‐dysregulated group were significantly reduced. Conclusion: MBCT‐C may facilitate clinically meaningful changes in the brain structural network in mood‐dysregulated individuals.